2017
DOI: 10.1111/ijlh.12727
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of hemostatic abnormalities in major orthopedic surgery patients treated with edoxaban by APTT waveform

Abstract: Introduction: An analysis of the activated partial thromboplastin time (APTT) in major

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…The APTT was measured using the APTT-SP® including silica as an activator of FXII and synthetic phospholipids (Instrumentation Laboratory, Bedford, MA, USA) using an ACL-TOP® system (Instrumentation Laboratory). After measuring the APTT, we performed a waveform analysis based on the results of each APTT assay [15, 19]. Three types of curves are shown on the monitor of the ACL-TOP® system (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The APTT was measured using the APTT-SP® including silica as an activator of FXII and synthetic phospholipids (Instrumentation Laboratory, Bedford, MA, USA) using an ACL-TOP® system (Instrumentation Laboratory). After measuring the APTT, we performed a waveform analysis based on the results of each APTT assay [15, 19]. Three types of curves are shown on the monitor of the ACL-TOP® system (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The ACL TOP analyzer for the using APTT-synthetic phospholipids (SPs) recently showed the associated first- and second-derivative peaks (1 st and 2 nd DPs, respectively) [13] It has been reported that the evaluation of the 1 st and 2 nd DPs in the APTT is valuable for diagnosing coagulation factor abnormalities and monitoring anti-Xa inhibitor [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is considered unnecessary to monitor patients receiving DOACs, major bleeding is sometimes observed in the patients treated with DOACs. 32 Low levels of anti-Xa activity may be risk of the onset of deep vein thrombosis 33,34 and a prolong APTT-CWA peak time may be a risk factor for major bleeding 35 in orthopedic patients treated with anti-Xa inhibitors. Warfarin decreased the height of the first and second DC in the APTT-CWA and prolonged the width of the first DC in the APTT-CWA, while edoxaban prolonged the peak time of the first and second DC in the APTT-CWA ( Figure 7).…”
Section: Monitoring For Anticoagulant Therapymentioning
confidence: 99%
“…Warfarin decreased the height of the first and second DC in the APTT-CWA and prolonged the width of the first DC in the APTT-CWA, while edoxaban prolonged the peak time of the first and second DC in the APTT-CWA ( Figure 7). 35 These differences in the APTT-CWA of patients treated with anti-Xa inhibitors and those treated with warfarin reflect to the difference in the effects of these drugs. That is, patients with anti-Xa inhibitors are considered to have a lower bleeding tendency.…”
Section: Monitoring For Anticoagulant Therapymentioning
confidence: 99%
“…Many previous reports have discussed the clinical application of CWA in patients with disseminated intravascular coagulation, [27][28][29] and recently, the use of CWA for evaluating the anticoagulant effects of direct oral anticoagulants has been described. 30,31 Unlike previous reports, the current report employed a unique approach to CWA including no smoothing procedure and template matching that uses whole multiple parameters instead of a few selected parameters. To our best knowledge, this is the first report which applying a concept of template matching to CWA.…”
Section: Thrombosis and Haemostasismentioning
confidence: 99%